2004
DOI: 10.1029/2004gl021030
|View full text |Cite
|
Sign up to set email alerts
|

Slip tapers at the tips of faults and earthquake ruptures

Abstract: [1] Slip gradients near the tips of earthquake ruptures and faults are typically linear. For non-interacting faults or earthquake ruptures, tip tapers are scale invariant, and about 1 -2 orders of magnitude larger for faults than for earthquakes. For fault tips interacting with other faults, the taper can be as much as a factor of 10 greater than for non-interacting faults. For earthquake ruptures, taper is also greater by as much as a factor of 10 for tips of rupture segments in the interior of the main ruptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 25 publications
(23 reference statements)
4
48
0
Order By: Relevance
“…This made a number of predictions of the scaling relations of faults including the fault length with displacement and the distribution of displacement along the fault length. Many of these relations have support from subsequent field data [ Vermilye and Scholz , 1998; Manighetti et al , 2004; Scholz and Lawler , 2004]. Scholz et al [1993] also made predictions regarding the scaling of the damage zone width with fault length.…”
Section: Introductionmentioning
confidence: 78%
“…This made a number of predictions of the scaling relations of faults including the fault length with displacement and the distribution of displacement along the fault length. Many of these relations have support from subsequent field data [ Vermilye and Scholz , 1998; Manighetti et al , 2004; Scholz and Lawler , 2004]. Scholz et al [1993] also made predictions regarding the scaling of the damage zone width with fault length.…”
Section: Introductionmentioning
confidence: 78%
“…(e.g., Manighetti et al, 2001aManighetti et al, , 2009Manighetti et al, , 2015Martel and Shacat, 2006;Muraoka and Kamata, 1983;Nicol et al, 2005;Peacock and Sanderson, 1996;Scholz and Lawler, 2004;Soliva and Benedicto, 2004, for normal faults;e.g., Bü rgmann et al, 1994;Farbod et al, 2011;McGrath and Davison, 1995;Pachell and Evans, 2002;Peacock, 1991, for strike-slip faults; e.g., Davis et al, 2005;Ellis and Dunlap, 1988;Shaw et al, 2002, for reverse faults). Furthermore, the displacement-length profiles have been shown to taper in the direction of long-term fault propagation (e.g., Davis et al, 2005;Manighetti et al, 2001a).…”
Section: Discussionmentioning
confidence: 99%
“…Because the envelope shape of displacementlength distributions is generic, along fault static stress gradients must also be. To reconcile the on-fault stress variability with the fairly linear scaling relation that is observed for all faults between their maximum displacement and their length (references in introduction), it has been suggested that the excess on-fault stresses that result from the gradual displacement decrease along the fault, are diffused off the fault, in the host rocks, where they produce microscopic and macroscopic ''damage'' fractures, faults and possibly other types of deformation (e.g., Cooke, 1997;Granier, 1985;Manighetti et al, 2004;Scholz and Lawler, 2004). Off-fault stress and strain diffusion might dominantly occur during repeated earthquakes on a fault (e.g., Cappa et al, 2014 and references therein;Manighetti et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, these structures are approximated as two‐dimensional slip surfaces. The classical understanding of fault growth relates fault length linearly to accumulated displacement due to episodically recurring earthquakes (e.g., Bürgmann et al, ; Cowie & Scholz, ; ; Manighetti et al, , ; Norris & Toy, ; Perrin, Manighetti, Gaudemer, et al, , Perrin, Manighetti, Ampuero, et al, ; Peacock, ; Peacock & Sanderson, ; Scholz & Lawler, ; Segall & Pollard, ). A gradual extension in fault length increases the fault surface area, which augments its potential to generate bigger earthquakes.…”
Section: Introductionmentioning
confidence: 99%